Evaluation of ERP Oracle Netsuite System for Purchasing Management Module at PT PQR using UTAUT2 Method - Richard Richard; Indira Damayanti; Mutia Annisa Nabilla; Almaida Aviani (LPPM Universitas Islam 45 Bekasi, 2022)
The purpose of the study was to evaluate the acceptance, use, and behavior of users towards the use of ERP Oracle NetSuite systems in the Purchasing Management module by analyzing how UTAUT2’s variables affected the user acceptances towards ERP Oracle NetSuite. The research method used is the UTAUT2 method, by conducting field studies to obtain information related to PT PQR and literature studies to support the theoretical data collection and analysis method to measure the user acceptance of ERP in the Oracle NetSuite Purchasing Management module system. In this study, 52 samples were collected using the saturated sample technique questionnaires. The data was analyzed using SEM-PLS with SmartPLS 3.0. The conclusion obtained from the results of this study is to focus more on improving performance expectancy, habit, and behavioral intention in using Oracle NetSuite ERP.